Paclitaxel-octreotide conjugates inhibit growth of human non-small cell lung cancer cells in vitro - Sun, M.L.; Wei, J.M.; Wang, X.M.; Li, L.; Wang, P.; Li, M.; Yi, C.H. (Experimental Oncology, 2007)
Aim: To evaluate the effects of paclitaxel-octreotide conjugates on the growth of cultured non-small cell lung cancer cells. Methods: RT-PCR was performed to detect mRNA for the subtypes of the human somatostatin receptor (SSTR) using specific primers. MTT-based cytotoxicity assay was used to evaluate the cell viability after treatment with paclitaxel and the conjugates. Cell cycle perturbations were determined using a Fluorescence-Activated Cell Sorter. Results: Non-small cell lung cancer A549 and Calu-6 cells expressed mRNA for SSTR2 and SSTR5. Paclitaxel and the conjugates effectively inhibited the growth of A549 and Calu-6 cells in a concentration- and time-dependent manner. In SSTR-negative fibroblasts, the conjugates were less cytotoxic than paclitaxel. The conjugates and paclitaxel could induce the increase of G2/M phase ratio in A549 cells. Conclusion: The paclitaxel-octreotide conjugates can be used as selective-targeted chemotherapeutic agents for treating non-small cell lung cancer. Цель: оценить эффект конъюгатов паклитаксела-октреотида на рост культивированных клеток немелкоклеточного рака легкого человека. Методы: для определения мРНК подтипов рецептора соматостатина человека (SSTR) применяли ОT-ПЦР. Анализ цитотоксичности в МТТ-тесте применяли для оценки выживаемости клеток после их инкубации с паклитакселом и конъюгатами. Нарушения клеточного цикла определяли с применением FACS — клеточного сортера. Результаты: установлено, что клеточные линии немелкоклеточного рака легкого A549 и Calu-6 экспрессируют SSTR2 и SSTR5 мРНК. Отмечено эффективное дозо- и времязависимое угнетение роста клеток A549 и Calu-6 паклитакселом и конъюгатами. Для SSTR-негативных фибробластов конъюгаты менее цитотоксичны, чем паклитаксел. Конъюгаты и паклитаксел могут индуцировать повышение соотношения фаз G2 /M в клетках A549. Выводы: конъюгаты паклитаксел-октреотида могут быть использованы как селективные химиотерапевтические агенты для воздействия на немелкоклеточный рак легкого.